2023
DOI: 10.1021/acsanm.2c05581
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Supported Tin Single-Atom Catalysts for CO2 Hydrogenation to HCOOH: A Theoretical Investigation of Performance under Different N Coordination Numbers

Abstract: The effects of the adjustment of the N coordination number in Sn single-atom catalysts toward the activity and selectivity of CO2 hydrogenation to HCOOH are systematically explored via density functional theory calculations. The stability of the studied catalysts was evaluated by formation energy calculations, and the calculated results indicated that Sn-N x C4–x -G (x = 1–4) are structurally stable. Through the discussion of the reaction mechanism, the optimal path of CO2 hydrogenation to HCOOH on all the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The E a value of RDS on it is 0.98 eV, which is lower than that on some reported catalysts, e.g., hydrogen-covered Pd(111) (1.40 eV), 47 Fe x Zr 1−x O 2 (1.59 eV), 48 and TiO 2 supported Ru 2 cluster (1.10 eV). 49 Furthermore, the activity of SnZnN 6 /G is superior to that of Sn-N 1 C 3 -G (1.10 eV), 27 the most active catalyst in the SnNC system, and it indicates that the activity of SnZnN 6 /G is superior to that of Sn SAC. The above analysis demonstrates that constructing Sn−M DACs by combining Sn with suitable TMs can effectively modulate catalytic performance.…”
Section: Computational Detailsmentioning
confidence: 98%
See 2 more Smart Citations
“…The E a value of RDS on it is 0.98 eV, which is lower than that on some reported catalysts, e.g., hydrogen-covered Pd(111) (1.40 eV), 47 Fe x Zr 1−x O 2 (1.59 eV), 48 and TiO 2 supported Ru 2 cluster (1.10 eV). 49 Furthermore, the activity of SnZnN 6 /G is superior to that of Sn-N 1 C 3 -G (1.10 eV), 27 the most active catalyst in the SnNC system, and it indicates that the activity of SnZnN 6 /G is superior to that of Sn SAC. The above analysis demonstrates that constructing Sn−M DACs by combining Sn with suitable TMs can effectively modulate catalytic performance.…”
Section: Computational Detailsmentioning
confidence: 98%
“…21−26 Liang et al have proved that SnNC SACs have high activity and selectivity for CO 2 hydrogenation to HCOOH. 27 However, due to their single active site, SACs have difficulty breaking the unfavorable linear scaling relationship between intermediates adsorption in complex reactions involving multiple intermediates. 28,29 As an extension of SACs, dual-atom catalysts (DACs) provide a possibility to solve this problem, and they have aroused much interest among researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Sn-based SACs have demonstrated remarkable catalytic activity in various chemical reactions [ 6 ]. For instance, Liang et al conducted a systematic study on the effects of altering the nitrogen coordination number in Sn single-atom catalysts (SACs) to investigate the activity and selectivity of CO 2 hydrogenation to formic acid (HCOOH) [ 7 ]. Tang et al conducted a comprehensive theoretical investigation on the performance of Sn single-atom catalysts (SACs) in the oxygen reduction reaction (ORR) using an associative four-electron mechanism [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, graphene will have some vacancies in the preparation process, so it is regarded as a suitable carrier for anchoring metal atoms to facilitate catalysis of diverse reactions. , Simultaneously, by adjusting the coordination atoms (N, O, S, P, etc.) to modify the local electronic structure of the active site, the catalytic performance of SACs can be improved to a certain extent. Moreover, it has been proved that the N atom with large electronegativity is an effective dopant to adjust the catalytic activity of SACs. REMs anchored into N-doped graphene have been developed and have demonstrated excellent performances in a wide range of catalytic processes. , For example, Li et al synthesized dispersed Ce atoms catalyst anchored into N-doped graphene, which exhibited remarkable activity in the oxygen reduction reaction . Liu et al also successfully synthesized Y/Sc SACs on N-graphene, confirming that it showed excellent catalytic activity in nitrogen reduction reaction and CO 2 RR .…”
Section: Introductionmentioning
confidence: 99%